Analisis Pengetahuan dan Sikap Siswa SMS yang Berisiko Terjadinya Pernikahan Usia Dini - Alma, Lucky Radita; Kartikasari, Dhian; Ulfa, Nurnaningsih Herya (Preventia: The Indonesian Journal of Public Health, 2020)
Kedungkandang sub-district is one of the sub-districts in Malang which increases the level of expenditure at the initial level and less than 20 years in Malang. This study aims to understand the relationship between student's knowledge and attitudes with the risks associated with early marriage. The population in this study were high school and vocational high school and vocational high school students Wisnuwardhana. 107 samples were determined using a simple random sampling technique. Data analysis using chi-square test. The result were most of students had good knowledge (61.7%), unsupportive attitudes (52.3%) and motivation did not support early marriage (57.9%). The results of the analysis obtained from the results of research on the relationship at risk of early marriage.